The Relationship between Drug Adherence and Blood Pressure in Hypertensive Patients - Noviyana Cindy Aorazizah; Supratman Supratman (Indonesian Journal of Global Health Research, 2025)
Hypertension is a long-term health condition that cannot be completely cured. However, individuals can effectively manage their blood pressure by undergoing prolonged or even lifelong medication therapy to keep it under control. This study aims to determine the adherence to taking medication in hypertensive patients at the Kartasura Health Center, Sukoharjo Regency. The study utilized a simple random sampling method to collect data, involving a total of 96 selected respondents. Data were collected in November – December 2024 using the MMAS-8 questionnaire (Morisky Medication Aderence Scale) and direct blood pressure measurement. The results of this study show that most of the respondents are women (58.3%), most of them are in the category of low compliance level (82.3%). The results of the statistical analysis yielded a p-value of 0.861, indicating that no significant correlation was found between adherence to medication and blood pressure levels among individuals diagnosed with hypertension. This study concluded that blood pressure in hypertensive patients will be stable if medication adherence is carried out properly.